أثر التغيير في استعمالات الأراضي في بعض خواص التربة الفيزيائية والكيميائية - بركات, منى; علي, حيدر; عيسى, ربا (Latakia University Journal -Biological Sciences Series, 2019)
تتعرض ترب الغابات والنبت الطبيعي في الساحل السوري إلى انتهاكات واضحة متمثلة بالتعدي المستمر والمتزايد وذلك بتحويلها إلى ترب زراعية فضلاً عن الحرائق المفتعلة، سيكون لهذا تأثيرات سلبية على خواص تلك الترب. يهدف هذا البحث إلى دراسة تأثير التغيير في استعمالات الأراضي في بعض خواص التربة. تم تحديد (20 موقع 10منها مواقع غابات و10نبت طبيعي) تم تحويل جزء منها الى تربة زراعية (منطقة القرداحة). جمعت عينات ترابية من الغابة والنبت الطبيعي وكذلك من التربة الزراعية التي حولت اليها ومن عمق 25-0سم. أجريت على عينات التربة التحاليل التالية: المادة العضوية، الكثافة الظاهرية، التوزع الحجمي للحبيبات الفردية، متوسط قطر التجمعات الموزونة، وقد تم استخدام الغابة والنبت الطبيعي كشاهد للمقارنة. أظهرت نتائج الدراسة إلى تدهور خواص التربة نتيجة تحويل الغابة والنبت الطبيعي إلى أرض زراعية حيث انخفض كل من: الكربون العضوي، ونسب الطين والسلت، ومتوسط قطر التجمعات الموزونة، وبشكل معنوي في التربة الزراعية مقارنة مع تربة الغابة وتربة النبت الطبيعي فقد بلغت أعلى نسبة انخفاض للخواص المذكورة على التوالي في المواقع المدروسة لدى تحويل منظومة الغابة والنبت الطبيعي إلى منظومة زراعية 77.42)%)، %31.81)) ((%52.65، 84.07)%)، كذلك أظهرت نتائج الدراسة ارتفاع كل من الكثافة الظاهرية ونسب الرمل، في التربة الزراعية مقارنة بتربة الغابة وتربة النبت الطبيعي، وكانت أعلى نسبة لارتفاع الكثافة الظاهرية في المواقع المدروسة لدى تحويل منظومة الغابة ومنظومة النبت الطبيعي إلى تربة زراعية (%26.08)، بينما وصلت نسبة الارتفاع 72.43)%) بالنسبة للرمل. The forests and natural plantations in Syrian coast are exposed to violations appeared by continuous and increasing erosion by transforming them into agricultural soils This will, have negative effects on the properties of these soil. This research aims to study the effect of change in land use in some soil properties. (20 sites were identified as 10 forest sites and 10 natural plants), some of them were transformed into agricultural soil (from Qardaha region), soil samples were collected from forest, natural vegetation and agricultural soil which transferred from them at (0-25 cm depth). Soil bulk density, distribution of individual particles, mean wight diameter were performed. Forest and natural plantation were used as control. The results showed deterioration of soil properties due to conversion of forest and natural plantation to agricultural land. Both organic carbon, clay and silt ratios, main wight diameter, were decreased significantly in agricultural soils compared to natural plantation and forest soils. The properties mentioned has reached respectively the highest rate of decline in the studied sites when converting the forest system and natural plant to an agricultural system (%77.42),(%31.81) ),(%52.65), (%84.07). The results showed as well, an increase in bulk density, sand ratios in agricultural soil compared to the forest and natural plantation soil. The highest density was observed in the studied sites when converting the forest system and the natural plant system into agricultural soil (%26.08) while the ratio was (%72.43) for sand.